Investigating new structures from genetic algorithm in optimization Exploitation of tanks - A. Afshar; M. Shafie; O. Bozorg hadad (Fanāvarī-i āmūzish, 2007)
By building large dams in different countries of the world, increasing the efficiency and effectiveness of these reservoir systems and maximizing the benefits of them is one of the most important issues studied in recent years. Evolutionary algorithms such as genetic algorithms (GA) are used in many scientific and engineering categories as search and optimization tools. Many applications of these methods have been reported on the issue of optimal utilization of reservoirs. In this research, an attempt is made to evaluate and evaluate the potential of new and applied formulations of genetic algorithm in solving engineering problems, to provide a new structure in order to optimize the operation of reservoirs using GA. In this study, new structures of the genetic algorithm are examined by performing different sensitivity analyzes and the best of them will be used to determine the optimal release of reservoir outflows. The results show that GA has the ability to provide good responses in the optimal use of reservoirs. Based on these results, the genetic algorithm with elitism, along with the two-point shear displacement operators and the low probability mutation, produces the best response. These results indicate the relatively good potential of genetic algorithms in solving large-scale problems that have complex objective functions.